2022
DOI: 10.3389/fimmu.2022.960918
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional dynamics and epigenetic regulation of E and ID protein encoding genes during human T cell development

Abstract: T cells are generated from hematopoietic stem cells through a highly organized developmental process, in which stage-specific molecular events drive maturation towards αβ and γδ T cells. Although many of the mechanisms that control αβ- and γδ-lineage differentiation are shared between human and mouse, important differences have also been observed. Here, we studied the regulatory dynamics of the E and ID protein encoding genes during pediatric human T cell development by evaluating changes in chromatin accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 111 publications
(139 reference statements)
1
13
0
Order By: Relevance
“…Analyses from our lab showed that these findings from mouse studies are mirrored in human thymocytes, with immature TCRγδ+CD1+ thymocytes displaying much higher levels of EGR1-3 and ID3 compared to βselected ISP thymocytes [134]. In addition, using single cell data we discovered a strong but highly transient upregulation of ID3 in cells undergoing β-selection [88], which further confirms that ID3 is expressed in the course of commitment to both αβ and γδ lineage. Ectopic expression of ID3 in CD34+ fetal liver cells or CD34+CD1-HSPCs in the FTOC system has been shown to prevent T lineage commitment and interferes with the induction of TRD rearrangements [149,150], which can probably be attributed to ID3-mediated inhibition of E protein activity as well as the downregulation of RAG1/2 [149] (Figure 2C).…”
Section: Transcriptional Regulation Of γδ Lineage Commitmentsupporting
confidence: 66%
See 2 more Smart Citations
“…Analyses from our lab showed that these findings from mouse studies are mirrored in human thymocytes, with immature TCRγδ+CD1+ thymocytes displaying much higher levels of EGR1-3 and ID3 compared to βselected ISP thymocytes [134]. In addition, using single cell data we discovered a strong but highly transient upregulation of ID3 in cells undergoing β-selection [88], which further confirms that ID3 is expressed in the course of commitment to both αβ and γδ lineage. Ectopic expression of ID3 in CD34+ fetal liver cells or CD34+CD1-HSPCs in the FTOC system has been shown to prevent T lineage commitment and interferes with the induction of TRD rearrangements [149,150], which can probably be attributed to ID3-mediated inhibition of E protein activity as well as the downregulation of RAG1/2 [149] (Figure 2C).…”
Section: Transcriptional Regulation Of γδ Lineage Commitmentsupporting
confidence: 66%
“…Moreover, based on elevated levels of germline transcription upon E protein transfection, it was hypothesised that E2A and HEB regulate accessibility at recombination signal sequence (RSS) sites [87], which supports a local rather than global role of E proteins in the regulation of TCR locus rearrangement. Recent transcription factor footprinting analyses from our lab have predicted a large number of E2A binding sites throughout the TRD and TRG loci, which were associated with open chromatin and permissive histone marks in CD34+ thymocytes and could thus indicate involvement of the E protein in controlling chromatin state and germline transcription at the loci in developing thymocytes [88] (Figure 2B). Furthermore, using single cell data, we found that E2A RNA levels were positively correlated with those of TRGC2, which points towards a role of E2A in TRG germline transcription or expression of the rearranged γ-chain [88].…”
Section: Regulation Of Trd/trg Rearrangementmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent single cell sequencing resources demonstrating the diversity of human thymus tissue are incongruous with our current framework of thymus structure and organization [7][8][9][10][11][12][13][14][15][16][17][18][19] which describes a general migratory path a thymocyte takes through the cortex and medulla during conventional αβT cell development. Recent spatial transcriptomic sequencing of human fetal and postnatal thymus has demonstrated that a deeper granularity of thymic niches is present within the tissue and that these niches evolve during fetal development to support different waves of non-conventional T cells 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Receptor 1 (IFNGR1), and that elevated IFN-γ production is protective against infection with malaria (41-43). In addition, TCF3 was shown to promote the development of γδ T cells, differentiation of memory CD8 T cells, and increase γδ T cells and CD8 + T cell responses in children with SMA (44)(45)(46)(47). Although not reported in malaria, human ZBTB6 was one of the most differentially expressed genes in the whole blood of patients with Crohn's disease (48).…”
Section: Discussionmentioning
confidence: 99%